(3Gdbhd GdSOjO aj CNjGQ GdEeGA hGdYHjOs - (3eXaQ GdOjf eMehO Hf CMeO GdYjfJGHi GdeYQha HGdGeTGWis; (3GHf SGYO GdSfLGQj , eMeO Hf EHQGgje Hf SGYO GdCfUGQj GdSfLGQj, GHf GdGcaGfj CHh YHO Gddg,J (B749 (3g` s
(3ChdgG (B:s
(3hHYO abO hbYJ Ydi hQbGJ ddTjN eMeO Hf EHQGgje Hf SGYO GdCfUGQi GdeYQha HGHf GdCcaGfi ai ChUGa GdQbjb aCQOJ Cf CVe EdjgG ahGFO egeI hQJHJg Ydi ebOeI hKdGK aUhd hNGJeI s
(3BNQgG (B:s
(3hGSJMVQ eG PcQ ajg agh LOjQ HYhf Gddg Cf jQRb GdJCjjO ai TQ GdEeGA hGdYHjO hCf jba Ydi LhgQjI GdQbjb heYGfjg heG jMJhi Ydjg ef GdCNdGb hGdWHGY hGdeYGQa hGddg Gdehab hGdgGOi ddUhGH s
(3Hg HYV GdChQGb GdMHQ ajgG bO EMJQGbs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdeYGQa GdYGeIs